Medical students utilization of e-learning re-sources; is it an informal curriculum? - Yaseen, Maria; Bano, Misbah; Jawaid, Masood (International Journal of Medicine, 2017)
Background: E-learning refers to the use of Internet technologies to deliver a broad range of solutions that enhance knowledge and per-formance of learners. This mode of learning can be used by institutions to improve the efficiency and effectiveness of educational inter-ventions in the face of the social, scientific, and pedagogical challenges. Worldwide, it has gained popularity in the past few decades; however, its use is highly variable among the medical schools of Pakistan. Currently, a very few number of institutions have adopted it officially in their curriculum. Despite this, many students use different E Learning resources to enhance their learning.Objective: To find out about the online resources utilized by the medical students in addition to their traditional medical curriculum to enhance their learning.Method: In this cross-sectional study, 300 participants from Dow Medical College and Jinnah Sindh Medical Universities were included after taking informed consent. A self-administered questionnaire which consists of demographic information, years of study and online resources with their usage details by the students for different subjects of basic and clinical sciences were documented.Results: Almost all the students reported to use some form of eLearning to enhance their medical understanding. The most frequently used electronic resources were Google images (61.7%) and Wikipedia (50.3%). Mostly, the students used YouTube (25.7%) for animations; Kaplan (27%) and Dr. Najeeb (15.6%) for video lectures. However, Audio lecture by Goljan (17.7%) was the only resource for podcast learning. Among discussion forums, Facebook groups (16.3%) were most popular and among static websites, Medscape (4.3%), PubMed (2.5%), WebMD (1.3%) were the most commonly used ones.Conclusion: All of the medical students used some form of eLearning in medical education in addition to their formal curriculum. This way of learning should be further implemented in the form of formal curriculum as e-learning modules for basic and clinical sciences to make learning easier, engaging and innovative for the 21st century learners.